Embedded atom method interatomic potentials fitted upon density functional theory calculations for the simulation of binary Pt-Ni nanoparticles - Symianakis,E; Kucernak,A (Computational Materials Science, 2017)
Embedded Atom Method (EAM) potentials have been fitted for the atomistic simulation of small, 2–5 nm, binary, PtANi, nanoparticles completely from Density Functional Theory (DFT) total energy calculations.The overall quality of the DFT calculations and the final potential is obtained through the independentcalculation of an array of properties of the pure metals and the stable alloys, which arenormally used for the fitting of interatomic potentials. The ability of the fitted potentials to simulatenanostructures is evaluated by the reproduction of binary nanoslabs with thickness 1 nm, and nanoparticlesin the extreme case of the smallest icosahedrons possible, with diameter 0.6 nm. The usedapproach requires high quality of convergence but otherwise low cost DFT as it is based on static totalenergy calculations. It also provides objective criteria for the evaluation of the fitted potentials during fittingand has been implemented with the open source code GULP